Formulation and In-Vitro Penetration Test of Ketoconazole Nanoemulsion - Ernoviya; Afriadi (Talenta Publisher, 2020)
This study was aimed to formulate ketoconazole into nanoemulsion form and to compared the penetration ability of each formula with ketoconazole cream on the market as control. Formulation of nanoemulsion uses spontaneous methods and and also measurement of particle using the Particle Size Analyzer (PSA). In vitro penetration test used Franz diffusion cells. The results showed that nanoemulsion of each formula had different particleÂ sizes, it was due to the distress of homogenizing two different systems, the duration and speed of stirring also affect the homogenity. The higher concentration of surfactant (tween 80) in the nanoemulation preparation could increasing the penetration ability of the preparation, but if the concentration exceeds the critical micelle concentration (CMC), a tight surfactant matrix (tween 80) will be formed which causes the release of ketoconazole to be slowed. Based on the observation, the highest penetration test was formula F3 as many as 4,268.01 Âµg/cm.